Maximization of the Weizsacker-Williams Equation in Electron-Positron Annihilation, and probability of creation of heavy quarks (SCIÉNDO INGENIUM, 2021)
The present work was determined and simulated the equation for the creation of heavy quarks obtained by the annihilation of particle-antiparticle, exactly electron positron in hadrons. The method used to determine the formulation has been by maximizing the Weizsacker-William’s equation, an approximation of the cross section for various events given by relativistic leptonic collisions; The Altarelli-Parisi technique was applied, which provides us with the probability density function to generate a pair of quarks   , in the final state of the system and it was simulated by obtaining the programming code in MatLab. The computer program made it possible to diagram the probability density curve, under the cross section of said production. The present work considers kinematic variables and relativistic dynamics in all collisions of leptons at high energy, as well as the principles of energy-moment conservation evidencing the generation of new heavy elementary particles.
Keywords: quarks; Weizsacker-Williams; Altarelli-Parisi; effective section and dispersion